2021
DOI: 10.1186/s40545-021-00303-0
|View full text |Cite
|
Sign up to set email alerts
|

National Health Insurance Fund’s relationship to retail drug outlets: a Tanzania case study

Abstract: Background Achieving universal health coverage will require robust private sector engagement; however, as many low- and middle-income countries launch prepayment schemes to achieve universal health coverage, few are covering products from retail drug outlets (pharmacies and drug shops). This case study aims to characterize barriers and facilitators related to incorporating retail drug outlets into national prepayment schemes based on the experience of the Tanzanian National Health Insurance Fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 12 publications
(6 reference statements)
1
26
0
Order By: Relevance
“…Although there was a higher overall health insurance coverage (75%), those who were undergoing emergency surgery had 33.3%, which is comparable to findings of another study done on surgical patients in Northern Tanzania (45.5%) and to Tanzania’s general population (32% in 2019) [ 34 , 35 ]. Patients are likely to have received their health insurance after being planned for elective surgery.…”
Section: Discussionsupporting
confidence: 75%
“…Although there was a higher overall health insurance coverage (75%), those who were undergoing emergency surgery had 33.3%, which is comparable to findings of another study done on surgical patients in Northern Tanzania (45.5%) and to Tanzania’s general population (32% in 2019) [ 34 , 35 ]. Patients are likely to have received their health insurance after being planned for elective surgery.…”
Section: Discussionsupporting
confidence: 75%
“…PPPs and NHI can be useful tools to reduce costs for clients and improve access to medicines when it is functioning well and has a high population coverage [ 42 – 44 ].However, at the moment many bottlenecks exist in the two study countries where NHI has been implemented for a longer time that limit its potential. Premiums paid by the insured are unaffordable to parts of the population, stockouts or lack of commodities at facilities force clients to buy out-of-pocket at non-accredited facilities, shortages of HCWs affect quality of services, a pro-urban distribution of health facilities results in clients needing to travel long distances to accredited facilities in rural areas, and delays in provider reimbursement by the NHI scheme result in co-payments by clients, denial or limiting of services, and long waiting times [ 39 , 40 , 45 , 46 ]. To fulfil its potential, governments ought to focus on tackling these bottlenecks.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of previous studies reported that access to free better quality free medical care is an important motivation for clinical trial participation [ 40 , 55 – 58 ]. In a developing country such as Tanzania, whereas the coverage of health insurance is low [ 59 ] and poor service delivery, it is justifiable for participants to mention free medical check-ups and care in the clinical trial as a benefit.…”
Section: Discussionmentioning
confidence: 99%